THE FLEXURAL BEHAVIOR OF SUSTAINABLE LIGHTWEIGHT CONCRETE HOLLOW CORE SLABS - Abdulhussein, Samer; Jaafar, Esraa; Rasheed, Maryam (Journal of Applied Engineering Science, 2024)
Hollow slabs are reinforced concrete slabs with voids that enable less concrete to be used. To promote sustainability goals, this type of slab reduces material use and enhances insulating characteristics. This paper presents an experimental program for studying the flexural behavior of the sustainable hollow Slab elements of lightweight concrete with three different ratios of mixes using additives to choose the best ratio, which is then compared to a solid model with the same concrete mix with the best characteristics to clarify the variations in the structural behavior of voided slabs. In this investigation, hollow slabs with circular plastic tubes of 50mm diameter and 1020 mm length were used, organized as continuous voids with 30 mm spacing between the tubes. Three slabs were created, each measuring 1020 mm long, 420 mm wide, and 100 mm thick. All three slabs were tested via four-point loading. The best mix ratio was chosen and used to build a robust model. To analyse the key advantages of this technology over typical solid slabs, this solid model was compared to the best-performing model among the three hollow core slabs. Several properties such as load-carrying capability, deflection, crack patterns, and failure modes were observed in all loading steps. The results showed that using uniformly distributed uniaxial voids in the slab reduced concrete use by 23% as compared to solid slabs, Notably, the specimen with 200 kg/m3 lightweight aggregate demonstrated greater crack distribution and crack breadth.